Mizoroki-Heck reaction of 1,2-disubstituted aryl alkenes: variables of synthesis, solvent and ligand modulation of reactivity - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil R.; Raut, Pallavi K.; Patil, Dharmaraj J.; Tv, Neethu; Sudhakaran, Shana; Iyer, Suresh (Synthetic Communications, 2020)
Reaction of aryl iodides with 1,2-disubstituted aryl alkenes in the presence of TBABr/TBACl gave high yields of the Mizoroki-Heck product. Phosphine ligands were used for the modulation of reactivity and stereoselectivity, for the reaction of 4-iodoanisole with cinnamaldehyde. tert-Bu3P.HBF(4)gave the highest E:Z ratio of 1:0.08. The use of PEG-200 and PEG-400 as solvent could activate the reaction of aryl iodides with various 1,2-disubstituetd aryl alkenes.
Keywords: 12-Disubstituted aryl alkenes; 400; ligand effect; Mizoroki-Heck reaction; PEG 200; TBABr

Bimetallic quantum dots (Cu-Pd, Ni-Pd) catalyzed reaction of bromo arenes with alkenes and aryl boronic acids - Raut, Pallavi K.; Meroliya, Heena K.; Dumbre, Swapnil R.; Patil, Vaishali N.; Solanki, Bhanupratap S.; Waghmode, Shobha A.; Iyer, Suresh (Indian Journal of Chemistry, 2023)
Bimetallic quantum dots (Cu-Pd and Ni-Pd) are active ligand-free catalysts for the alkenylation and arylation of aryl bromides. The catalysts are easy to synthesize by benign green protocols and characterized by various techniques. The bimetallic QD catalysts synthesized thus are superior to Pd(OAc)2 or other Pd NP catalysis of alkenylation reactions of aryl bromides with similar E-selectivity. The reaction of aryl bromide with aryl boronic acid is facile with high yields.
Keywords: Aryl bromides; Bimetallic QDs catalysis; Cu-Pd; Mizoroki-Heck; Ni-Pd; Suzuki coupling